2012
DOI: 10.1111/j.1365-2702.2012.04333.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the awareness, use and attitudes of women towards Down syndrome screening

Abstract: Discovering women's opinions and knowledge about PST will help healthcare providers determine their information needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
6
1
1
Order By: Relevance
“…We have found that participants' educational level was not associated with greater knowledge about DS or awareness of prenatal screening tests. These results are at variance with those from a study from Turkey, in which poor knowledge about prenatal screening for DS was found among women with a low socioeconomic background . However, our findings are in line with several other studies, which have found little correlation between overall education and health literacy.…”
Section: Discussioncontrasting
confidence: 53%
“…We have found that participants' educational level was not associated with greater knowledge about DS or awareness of prenatal screening tests. These results are at variance with those from a study from Turkey, in which poor knowledge about prenatal screening for DS was found among women with a low socioeconomic background . However, our findings are in line with several other studies, which have found little correlation between overall education and health literacy.…”
Section: Discussioncontrasting
confidence: 53%
“…This study results related to participants knowledge about screening tests support previous study findings. Nambiar 16 Majority of the patients in our study were aware about the disease but not about the measures to screen it. Thus, indicating health care providers can play a major role to educate women about screening of Down syndrome.…”
Section: Discussionmentioning
confidence: 86%
“…In study done by Emre et al, awareness about the first and second trimester screening was 21.6% and 59.7%, whereas use of them was 13.7% and 44.8%, respectively. 16 Nambiar et al, found that 64.7% of the women had right attitude towards screening tests and 46.1% patients had undergone the test. 9 Out of 217 pregnant women, 126 denied for Down syndrome screening test.…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43][44][45][46][47][48][49][50][51][52][53][54] Caregivers and patients, especially those of low socioeconomic status, prefer clinicians to make final decisions, and have little desire to learn more about treatment options. [51][52][53] Some clinicians approach genetic counseling as a means to reduce birth defects and deleterious genes in the population, and improve the affected family's quality of life, 50,[54][55][56][57][58] an attitude described as having eugenic tendencies. 55,56,58 This acceptability of eugenics is reportedly more common among clinicians in LMICs than HICs.…”
Section: Ethical Issuesmentioning
confidence: 99%